Treatment of Lumbosacral Radiculopathy with Acupuncture and Medical Herbs: Four Case Reports - Han Chae; Yoona Oh; Ji Won Choi; Soo Kwang An; Yeon Hak Kim; Jun Hwan Lee; Eunseok Kim; Byung Ryul Lee; Gi Young Yang (Medical Association of Pharmacopuncture Institute, 2022)
Lumbosacral radiculopathy (LR) is a musculoskeletal disorder or pain syndrome that is generally linked to the compression or irritation of the nerve root. There is a growing interest in the development of efficient acupuncture-based treatments for LR comparable to western medicine. Structured traditional Korean medical treatments including intensified acupuncture stimulus on the EX-B2 point using the G-shaped posture modified from the sitting posture were applied to four LR patients, and the outcomes were evaluated based on objective clinical endpoints including a numeric rating scale (NRS), the Oswestry disability index (ODI), the manual muscle test (MMT), neurological symptoms, and plantar photography. Patients showed improvements in NRS, ODI, MMT, and neurological symptoms without adverse effects during hospitalization and follow-up visits. Moreover, we observed substantial dissolvement of hyperkeratinization and parchedness of the soles of the feet, which was not reported previously. These four cases demonstrate the clinical usefulness of traditional medicine and the diagnostic applicability of plantar photography. However, further randomized controlled trials are required to confirm our findings.